2022
DOI: 10.1080/14756366.2022.2068147
|View full text |Cite
|
Sign up to set email alerts
|

Novel Sunifiram-carbamate hybrids as potential dual acetylcholinesterase inhibitor and NMDAR co-agonist: simulation-guided analogue design and pharmacological screening

Abstract: An efficient method for synthesising NMDAR co-agonist Sunifiram (DM235), in addition to Sunifram-carbamate and anthranilamide hybrids, has been developed in high yields via protecting group-free stepwise unsymmetric diacylation of piperazine using N -acylbenzotiazole. Compounds 3f , 3d, and 3i exhibited promising nootropic activity by enhancing acetylecholine (ACh) release in A549 cell line. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…These results indicated that d- serine plays a role in promoting activation of the NMDA receptor in the cochlea in physiological conditions [ 34 ]. Furthermore, the present results are in good agreement with previous studies showing that the NMDA receptors are located presynaptically and that acetylcholine is released by NMDA receptor stimulation in the brain [ 35 , 36 , 37 , 38 ]. Further studies on the localization of NMDA receptors in the salivary glands are needed.…”
Section: Discussionsupporting
confidence: 93%
“…These results indicated that d- serine plays a role in promoting activation of the NMDA receptor in the cochlea in physiological conditions [ 34 ]. Furthermore, the present results are in good agreement with previous studies showing that the NMDA receptors are located presynaptically and that acetylcholine is released by NMDA receptor stimulation in the brain [ 35 , 36 , 37 , 38 ]. Further studies on the localization of NMDA receptors in the salivary glands are needed.…”
Section: Discussionsupporting
confidence: 93%
“…The Ellman's assay results disclosed that derivatives 21 and 22 had AChE inhibitory activity and revealed higher inhibition percentages at the concentrations of 10 -4 and 10 -10 M while a lower inhibition percentage was obtained at 10 -12 . A series of novel sunifiram-carbamate and sunifiram-anthranilamide hybrids were designed and synthesized by Khalid A. Agha et al, 2022 [48] and evaluated for cholinergic activity. The authors concluded that introducing carbamate to the skeleton of synthesized targets resulted in good AChE inhibitory activity.…”
Section: Design and Synthesis Of New Ache Inhibitors During 2022mentioning
confidence: 99%
“…Compared to sunifiram (−4.5 kcal/mol) and the anthranilamide hybrid (−4.5 kcal/mol), it exhibited a molecular docking score −1.7 kcal/mol when docked to the glycine-binding pocket of the NMDA receptor. A series of novel sunifiram-carbamate and sunifiram-anthranilamide hybrids were designed and synthesized by Khalid A. Agha et al, 2022 [48] and evaluated for cholinergic activity. The authors concluded that introducing carbamate to the skeleton of synthesized targets resulted in good AChE inhibitory activity.…”
Section: Design and Synthesis Of New Ache Inhibitors During 2022mentioning
confidence: 99%
“…Thus, drugs to treat AD are based on their ability to inhibit cholinesterase enzymes, that is, acetylcholinesterase (AChE) and butyrylcholinesterase (BChE). , Nowadays, various drugs are used for the treatment of AD, including rivastigmine, donepezil, galantamine, and tacrine (Figure ). Synthetic organic chemists are working on new, chief, effective, and safe drugs for AD. , In the near past, our research group has reported imine-containing derivatives with promising biological activities. The present work is mainly focused on the synthesis of various thiosemicarbazone derivatives with anticholinesterase inhibitory potential.…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic organic chemists are working on new, chief, effective, and safe drugs for AD. 30 , 31 In the near past, our research group has reported imine-containing derivatives with promising biological activities. 32 35 The present work is mainly focused on the synthesis of various thiosemicarbazone derivatives with anticholinesterase inhibitory potential.…”
Section: Introductionmentioning
confidence: 99%